Clinical characteristics and colposcopy appearance of cervical intraepithelial neoplasia - Devi, Sangita; Sarker, Bidhan Krishna; Chakroborty, Sharmila; Rizwana Rahman, Ummul Sifat; Karmakar, Karuna Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer ranks as the second most prevalent cancer among women globally, particularly affecting those in economically disadvantaged regions. This study aimed to explore the epidemiology and clinical characteristics of cervical intraepithelial neoplasia (CIN). Methods: The cross-sectional study was conducted at the Colposcopy Center, Comilla Medical College Hospital, spanning from July 2015 to December 2015. Face-to-face interviews using a preformed questionnaire were employed for data collection. Inclusive criteria were followed for the enrolment of 200 participants, and a simple random sampling technique was utilized. Statistical analysis was planned in the SPSS program. Ethical clearance was obtained from the Comilla Medical College Hospital Ethical Review Committee to ensure confidentiality. Results: Among the 200 women studied, 15% were aged 20-29, 42% were 30-39, 38% were 40-49, and 5% were >50 years old. Illiteracy was prevalent in 30%, with 50% having primary education. CIN incidence was higher among illiterates and those in poor socioeconomic status (55.56%). Early sexual exposure, longer duration of exposure, and higher parity correlated with increased CIN risk. Non-use of contraception was observed in 30% of women, with 44.44% exhibiting CIN. Clinical features included predominant complaints of P/V discharge and various bleeding patterns. Conclusions: CIN prevalence was higher among 30-39-year-olds, emphasizing the impact of illiteracy, low socioeconomic status, early marriage, prolonged marital duration, high parity, and limited contraception use. Clinical manifestations primarily comprised P/V discharge and diverse bleeding patterns. This study underscores the need for targeted interventions addressing socio-demographic risk factors for effective cervical cancer prevention.